Efectos del enriquecimiento ambiental dependiente de la edad en el comportamiento, funciones cognitivas y neuroquímica. - Mora-Gallegosa, Andrea; Salas, Sofía; Fornaguera-Tríasa, Jaime (Revista Mexicana de Neurociencia)
Aging is associated with cognitive decline, which includes detrimental effects on learning and memory. It has been suggested that environmental enrichment may help to prevent the age-dependent declining, but there are contradictory results. This may be due, at least in part, to the wide spectrum of protocols of environmental enrichment used, but in particular to the age at which the enrichment starts. It has been reported that young animals may profit more from the environmental enrichment than mature ones at behavioral and neurochemical levels. Nevertheless, in our study, young and mature adult rats were submitted to environmental enrichment and both groups showed specific differences in habituation to a novel environment, working and reference memory in a spatial task. Young rats are clearly more active in a novel environment and radial maze test, compared to mature rats. Cognitive strategies related to working and reference memory were evaluated with radial maze test, and our results show that mature and young rats have different strategies to solve tasks, although young enriched rats have a better performance on this test. These results are correlated with DA turnover in ventral striatum (VS) and glutamate and GABA in hippocampus. Based in our results, earlier developmental periods are shown to be more sensitive to environmental enrichment, and on the other side, the cautiousness showed by mature rats seems to be an effective strategy to solve reference and working memory tasks.